Bringing context back into privacy regulation and beyond: About limitation on purpose as an (old) response to (new) data challenges - Karoline Krenn (economic sociology_the european electronic newsletter, 2019)
At the core of early privacy debates were state records, corporate records or survey data. The advancement of information technologies extended the availability of data. New technologies mediate many aspects of modern life and, thereby, enable data to be circulated. They provide access to very different types of data from very different sources.
Keywords: 300